2007
DOI: 10.3171/foc-07/07/e10
|View full text |Cite
|
Sign up to set email alerts
|

Skull morphology and its neurosurgical implications in the Hippocratic era

Abstract: ✓Differences in skull morphological characteristics among various human populations were first described by Herodotus of Halicarnassus. The Hippocratic treatise On Head Wounds (Περι των εν κεφαλη τρωματων) provided the first detailed description of human skull anatomy. The Hippocratic author presented the first systematic attempt to create a classification system of skull and cranial suture morphology. Detailed descriptions of various human skull ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Hippocrates was aware of the abnormal shape of the skull[2] and Sommerring,[3] observed that bone growth in the skull occurred primarily at suture lines and abnormal skull shape develop if the suture was replaced by bone.…”
Section: Introductionmentioning
confidence: 99%
“…Hippocrates was aware of the abnormal shape of the skull[2] and Sommerring,[3] observed that bone growth in the skull occurred primarily at suture lines and abnormal skull shape develop if the suture was replaced by bone.…”
Section: Introductionmentioning
confidence: 99%
“…The occipital lobe and the cerebellum structures are smaller structures compared to the temporal, frontal and parietal lobes, which can explain partly the poorer correlation coefficients. The fact that the cerebellum and the occipital lobe, in the heterogeneous model, may be "protected" by thicker bones at the back of the head may also be one explanation [10]. For the brain stem, we are comparing few values and small values (maximum SAR is inferior to 13% of the maximum value in the brain) so that is why we obtained a very poor correlation coefficient.…”
Section: Correlation Of Sar Distributions In the Brain Of Homogeneousmentioning
confidence: 87%
“…There are, however, complications associated with drilling a bur hole, 3 including skull fracture, enlarging pseudomeningocele, 3 infection, hemorrhage, 4,14 and death. 8 In addition, there is the potential to plunge the drill into the cranial cavity, lacerate the dura mater, and cause intracranial hemorrhage.…”
mentioning
confidence: 99%